Potential Output, EU Fiscal Surveillance and the COVID-19 Shock - Philipp Heimberger (Intereconomics, 2020)
This paper discusses how the technical foundations of the EU's fiscal rules constrain the fiscal space in EU countries in the context of the COVID-19 pandemic. We review the evidence on how estimates of potential output, which are at the heart of essential control indicators in EU fiscal surveillance, were revised in the ten years running up to the COVID-19 pandemic, and how these revisions affected the fiscal stance of EU countries. We provide first evidence for downward revisions in the European Commission's potential output estimates against the background of the COVID-19 shock across the EU27 countries, and we assess the potential consequences in terms of fiscal space. According to our results, one additional percentage point in predicted losses of actual output is associated with a loss in potential output of about 0.6 percentage points. Given the importance of model-based estimates in the EU's fiscal rules, avoiding pro-cyclical fiscal tightening will require that policymakers' hands are not tied by overly pessimistic views on the development of potential output.
Keywords: 330